The role of using the active methods of teaching science in cultivating the spirit of questioning research and achievement of Iranian students - Sahranavard, Maryam (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This study is in order to investigate the role of using the active methods of teaching science in cultivating the spirit of questioning-research and achievement of the students studying in the fourth grade of Iranian primary schools. The result shows that there is no significant difference between using active teaching methods as well as the spirit of Questioning-research in the students. In addition, there is no significant difference between using active teaching method and the score of students in the questionnaire for observing the questioning-research behavior. On the other hand, there is a significant difference between using inactive teaching method in the average score of students, which has been obtained from the achievement test.